Search for the FCNC charmonium decay J/ψ → D 0 μ + μ − + c.c. - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; X. C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; et al. (Journal of High Energy Physics)
Abstract Based on a data sample of (10087 ± 44) × 106 J/ψ events taken with the BESIII detector, we search for the flavor-changing neutral current charmonium decay J/ψ → D 0 μ + μ − + c.c. . No significant signal above the background is observed, and the upper limit on its branching fraction is set to be ℬ(J/ψ → D 0 μ + μ − + c.c.) < 1.1 × 10 −7 at the 90% confidence level. This marks the first search for a flavor-changing neutral current charmonium decay involving muons in the final state.